Territorial Dynamics of the Bay of Villefranche-sur-Mer (French Riviera) : from commercial and military vocation to tourism and sporting activities - Coglievina, Christian; Massiera, Bernard; Morales, Valérie; Ben Mahmoud, Imed (Anais Brasileiros de Estudos Turísticos, 2017)
The study concerns the dynamics of the coastal activities of the harbor of Villefranche-sur-Mer. Borrowing the concepts of territorialities (Gunn; Var, 2002) or competitiveness of an aera (Wackermann, 1989), revisited in a historical perspective and development of natural territories (Bessy 2008), it explored the problem of the littoral development in the light of its past activities. Three periods succeed each other from the international trade stop, then from the military presence to the current tourist vocation leading to its “sportivation”, especially in connection with the development of a local nautical offer. The articulation of these three periods determines the multiplicity of contemporary offerings which also involves the communities in a sustainability policy (sustainability of the sporting offer and protection of the marine biotope) through partnerships both scientific, National Center of Scientific Research (C.N.R.S.), and associations like A.I.D.A. (International Association for the Development of Apnea).